Metabolically Obese Normal-Weight Phenotype as a Risk Factor for High Blood Pressure: A Five-Year Cohort - Vera-Ponce, Victor Juan (2023)
“Background: The metabolically obese normal-weight (MONW) phenotype has been considered a risk factor for different chronic diseases, but its role in high blood pressure (HBP) is still unclear. The aim of the study is to determine if the MONW phenotype constitutes a risk factor for hypertension in Peruvian adults belonging to a 5-year cohort. Methods: This is a retrospective cohort study. A secondary analysis from the database of the PERU MIGRANT study was carried out from the MONW and non-MONW cohorts; after a 5-year follow-up, the appearance of HBP was evaluated in the subjects of both cohorts. To assess the strength and magnitude of the association, a Poisson regression model (crude and adjusted) with robust variance was used. The measure of association was the relative risk (RR). Results: The incidence of HBP was 11.30%. In the multivariable analysis, subjects with the MONW phenotype had a 2.879-fold risk of presenting HBP in 5 years compared with those who were not MONW at the beginning of the study; this was adjusted for categorized age, sex, group, and state of smoker and alcohol drinker (RR: 2.055; 95% confidence interval (CI): 1.118 - 3.777; P = 0.020). Conclusions: The presence of the MONW phenotype doubled the incidence of HBP, even after adjusting for other covariates. However, studies in this field should continue. If these findings are confirmed, it should be considered that presenting an adequate weight for height should not be interpreted as a condition free of metabolic alterations, so screening for hypertension should be carried out regardless of w“